الشيخ محمد زكرياحياته وجهوده العلمية في اللغة العربیة - Dr. Muhammad Ans (Al Manhal Research Journal, 2025)
This research examines Sheikh Muhammad Zakariya al-Kandahlawi’s significant contributions to the service and promotion of the Arabic language, with a particular focus on his scholarly commentary on Al-Muwatta of Imam Malik — the earliest systematically arranged Hadith collection in Islamic history. Composed in the Indian Subcontinent, his work not only elucidates the Hadith text but also engages deeply with core linguistic domains such as phonetics, morphology, syntax, and semantics. His precise treatment of issues such as the fāʿil (subject) in verbal sentences serves as a case study of his grammatical expertise. Through these examples, the study situates Sheikh Zakariya within the broader tradition of Hadith commentators whose linguistic analysis has shaped both religious understanding and Arabic scholarship in non-Arab regions. By exploring his methods, sources, and pedagogical approach, this research opens avenues for further investigation into the intersection of Hadith sciences and Arabic linguistics, as well as the spread of the Arabic language in non-Arab contexts.